Antecedent infections in Guillain‐Barré syndrome patients from south India. Issue 3 (26th July 2021) - Dutta, Debprasad; Debnath, Monojit; Nagappa, Madhu; Das, Sumit Kumar; Wahatule, Rahul; Sinha, Sanjib; Taly, Arun B.; Ravi, Vasanthapuram
Abstract: Guillain‐Barré syndrome (GBS) is the commonest post‐infectious inflammatory peripheral neuropathy with undiscerned aetiology. The commonly reported antecedent infections implicated in India include Campylobacter jejuni, chikungunya, dengue, and Japanese encephalitis (JE). In this study from south India, we investigated the role of these four agents in triggering GBS. This case‐control study was performed on 150 treatment‐naive patients with GBS and 150 age and sex‐matched controls from the same community. IgM immunoreactivity for C. jejuni, chikungunya, and dengue was detected by enzyme‐linked immunosorbent assay (ELISA) in serum of patients with GBS and control subjects. Immunoreactivity against JE was detected in serum as well as cerebrospinal fluid (CSF) from patients (n = 150) and orthopaedic control (n = 45) subjects. The immunoreactivity against infections was compared between demyelinating and axonal subtypes of GBS. Overall, 119/150 patients with GBS had serological evidence of antecedent infection. Amongst those with evidence of antecedent infection, 24 (16%), 8 (5%), and 9 (6%) patients were exclusively immunoreactive to chikungunya, JE, and C. jejuni, respectively. In the remaining patients (78/119), immunoreactivity to multiple pathogens was noted. Immunoreactivity to C. jejuni infection was found in 32% of GBS patients compared to 2.7% controls ( P  < .001), whereas to chikungunya virus was reported in 66.7% of patients with GBS compared to 44.7% controls ( P  = .006). Anti‐dengue immunoreactivity was significantly associated with the demyelinating subtype of GBS. Patients positive for JE IgM (CSF) manifested demyelinating electrophysiology. In this large case‐control study, immunoreactivity against multiple infectious agents was observed in a subset of patients. Chikungunya was the commonest antecedent infection, followed by C. jejuni .